Comparative Mechanical Characterization of M30 Concrete Grade by Fractional Replacement of Portland Pozzolana Cement with Industrial Waste Using CoCoSo and CODAS Methods. Issue 1 (November 2020) - Kumar Bagal, Dilip; Naik, Bibekananda; Parida, Biswajit; Barua, Abhishek; Jeet, Siddharth; Kumar Singh, Sangam; Kumar Pattanaik, Ajit
Abstract: Since last few years, marble has been deliberated as some of the utmost significant embellished constructing resources. Marble Powder (MP) and Fly Ash (FA) are nearly those materials, which creates health hazards and pollutes the environment. This present study targets to investigate the effect of marble powder and fly ash as fractional replacement of cement respectively in different concrete mixes. The M30 grade of concrete was chosen with a continual w/c ratio 0.43 where fractional replacement of Portland Pozzolana Cement with Marble Powder and Fly Ash is done in different proportion. After preparing the samples according to Taguchi's method orthogonal array, the mechanical characterizations are performed. Hardened concrete tests such as compressive strength, split tensile strength and flexural strength test have been piloted to appraise the mechanical properties of concrete. Two current multi-response optimization techniques were used i.e. Combinative Distance-based Assessment (CODAS) and Combined Compromise Solution (CoCoSo) method for optimization of process parameters. In order to outline comparative consequence of measured criteria a pairwise comparison matrix was used. The results of all tests were analyzed, comparison has done among concrete mixes and the conclusion is drawn.